Masjid Pusat Ekonomi Kerakyatan - Ngimadudin Ngimadudin (STAI Bumi Silampari, 2021)
Indonesia is the largest Muslim population in the world. With the largest Muslim population in the world, the country of Indonesia is take advantage of these conditions and can be an opportunity to develop the economy Sharia in Indonesia. With the existence of Islamic Economics, it can provide activities Islamic economy and adheres to Islamic principles, namely the Qur'an and Sunnah Hadith. The prolonged economic crisis that has occurred in Indonesia is still have not been able to find the light. Poverty at the bottom and tend to be marginalized from every community activity, this can lead to gap between the rich and the poor. Upgrade the community's economy means increasing the ability of the community by develop the potential of the community. Therefore Baitul Maal Mattamwil (BMT) also plays an important role in developing the Islamic Economy in Indonesia. Because this BMT will also be able to help in increasing the business economy in the community for the lower middle class, this assistance can also in the form of additional capital or financing to be able to improve a business.